2009
DOI: 10.1093/nar/gkp188
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry for enrichment and titration in massively parallel DNA sequencing

Abstract: Massively parallel DNA sequencing is revolutionizing genomics research throughout the life sciences. However, the reagent costs and labor requirements in current sequencing protocols are still substantial, although improvements are continuously being made. Here, we demonstrate an effective alternative to existing sample titration protocols for the Roche/454 system using Fluorescence Activated Cell Sorting (FACS) technology to determine the optimal DNA-to-bead ratio prior to large-scale sequencing. Our method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…A modification of this technique has been reported where nucleotides are detected and sorted using microfluidic techniques, but is further hampered by the need to use custom-built machinery for the sorting of these molecules17. An entirely different enrichment strategy is to physically purify molecules using beads coated in capture probes and sorting them using flow cytometry21; however, this approach also is limited to targets of a few kilobases per capture probe, necessitating thousands of probes to recover megabases of sequence22. An optimal system for enriching DNA would significantly increase the lengths of molecules that could be recovered per target probe.…”
mentioning
confidence: 99%
“…A modification of this technique has been reported where nucleotides are detected and sorted using microfluidic techniques, but is further hampered by the need to use custom-built machinery for the sorting of these molecules17. An entirely different enrichment strategy is to physically purify molecules using beads coated in capture probes and sorting them using flow cytometry21; however, this approach also is limited to targets of a few kilobases per capture probe, necessitating thousands of probes to recover megabases of sequence22. An optimal system for enriching DNA would significantly increase the lengths of molecules that could be recovered per target probe.…”
mentioning
confidence: 99%
“…This resulted in the following 16 bp oligonucleotide probes: FL_MID1, 5' Pacific Blue-ACTCAGACGAGTGCGT 3', (Thermo Fisher Scientific, Waltham, USA); FL_MID2, 5' Alexa488-ACTCAGACGCTCGACA 3' (Eurofins MWG Operon, Ebersberg, Germany); FL_MID4, 5' biotin-ACTCAGAGCACTGTAG (Eurofins MWG Operon); and FL_MID5, 5' BODIPY630/650-ACTCAGATCAGACACG (Eurofins MWG Operon). We have in previous publications demonstrated that FACS enrichment does not affect the GC content or sample complexity, in FACS sorted bead samples1016.…”
Section: Methodsmentioning
confidence: 92%
“…To remove labeling probes from flow-sorted beads these were washed three times in 0.1M NaOH and then three times in 1xAB with centrifugation steps between washes, as described above. In previous publications we have demonstrated that alkali wash is sufficient to remove the fluorescent labeling10. Sequencing primer was annealed to the beads, then the ‘standard-enriched' sample and the two flow-sorted samples were loaded onto separate lanes of a Picotiter plate and sequenced following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A/B linker) can be effectively used to identify DNA-carrying beads to simplify the titration step in Roche/454 sequencing and (more importantly) facilitate enrichment of pure samples with DNA-carrying beads produced by a shotgun sample preparation procedure [12]. In our current work we have taken this method further by showing that beads carrying a specific target DNA sequence can be collected for sequencing using flow cytometry and hence beads carrying an unspecific product that includes A or B linkers can be removed.…”
Section: Discussionmentioning
confidence: 99%
“…This is a quick, inexpensive way of ensuring that all of the analyzed beads carry DNA, without affecting the sequence quality [12]. Here, we present a method for selection and enrichment of beads with correct products on the surface, thus removing beads carrying unspecific sequences, which were not removed by standard gel purification protocols.…”
Section: Introductionmentioning
confidence: 99%